2009
DOI: 10.1111/j.1365-2923.2008.03253.x
|View full text |Cite
|
Sign up to set email alerts
|

Electives: isn’t it time for a change?

Abstract: Electives are a highlight of clinical training but probably often represent missed opportunities. There are both educational and moral reasons for seeking more considered approaches to reduce the 'medical tourism' that can result from the current largely ad hoc arrangements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
159
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(162 citation statements)
references
References 23 publications
3
159
0
Order By: Relevance
“…3,8,12,17 Our survey showed that local health professionals are often responsible for onsite supervision; this allows for a better understanding of the local context and for cultural and linguistic translation, 24 but emphasizes the need to have a shared understanding of students' roles and limitations. 3,17 Establishing specific learning objectives for GHEs in partnership with the host institution may help clarify the level of supervision required.…”
Section: Onsite Supervisionmentioning
confidence: 99%
“…3,8,12,17 Our survey showed that local health professionals are often responsible for onsite supervision; this allows for a better understanding of the local context and for cultural and linguistic translation, 24 but emphasizes the need to have a shared understanding of students' roles and limitations. 3,17 Establishing specific learning objectives for GHEs in partnership with the host institution may help clarify the level of supervision required.…”
Section: Onsite Supervisionmentioning
confidence: 99%
“…Medical students and residents continue to participate in global health activities, but they often do not have adequate preparation (Crump & Sugarman 2008; Unite for Sight 2010), which hampers their efficiency and effectiveness, and disproportionately consumes limited resources (Shah & Wu 2008;Dowell & Merrylees 2009). As educational institutions, we have not only an opportunity, but a responsibility to provide them with sound and rigorous training in global health that prepares them for work overseas and at home in an increasingly globalized community.…”
Section: Recommendationsmentioning
confidence: 99%
“…Additionally, curricula that teach global public health or clinical global health tend not to describe the processes, challenges, and practical issues involved in addressing the same issues within the US. Even the more recent articles proposing increased training opportunities in global health do not discuss US-based electives as part of a Global Health curriculum (Panosian & Coates 2006;Dowell & Merrylees 2009;Nelson et al 2011).…”
Section: Practice Pointsmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Additionally, authors have proposed distinct educational strategies 13 and standardized medical school-based curriculum guides. 14 …”
mentioning
confidence: 99%